Stepwise cox regression analysis in SPSS - Sampada Dessai (Cancer Research, Statistics, and Treatment, 2018)
This article is a beginners' guide for performing Cox regression analysis in SPSS. The article provides practical steps toward performing Cox analysis and interpreting the output of SPSS for Cox regression analysis. Along with it, the article touches on the test to be performed before performing a Cox regression analysis and its interpretation.